Occurrence of Arbuscular Mycorrhizal Fungi in Vegetables Grown in Nakornpathom Province, Thailand - Wijit Wonglumsom; Narakorn Surasorn; Amornthep Kochatung (Agriculture and Natural Resources, 2006)
Arbuscular mycorrhizal colonization in the roots and spore numbers in the rhizosphere of vegetables grown in Nakornpathom province of Thailand were studied. A percentage of fungal infection in the roots was analyzed by a staining method of Phillip and Hayman. A quantity of mycorrhizal spores was determined by a modification of a wet-sieving and decanting technique, and centrifugation method. Spore numbers (mean±SD) of garlic, Chinese kale and broccoli plants were 64.59±28.23, 64.09±36.62 and 45.70±33.01 spores per 100 grams of dry soil, respectively. Three genera of spores were identified from these plants, including Acaulospora, Gigaspora and Glomus with occurrence of individuals ranging from 48.05% to 100%. Internal vesicules and arbuscules of mycorrhizal fungi were observed only in garlic roots for all samples with the infection rates of 28.95±26.75%. There was no relationship between spore numbers and mycorrhizal colonization levels in the garlic plants. An occurrence of mycorrhizal spores in soils for cultivation of broccoli and Chinese kale did not affect the fungal colonization in the roots.